Pengaruh Perdagangan Internasional Dan Investasi Terhadap Kesejahteraan Ekonomi Indonesia Serta Negara ASEAN - Fitri Annisa; Hendra Ibrahim (JURNAL RISET MANAJEMEN (JURMA), 2024)
The developments in the current era make it easier for us to carry out trade, both national and international trade. But behind that, there is a match to this. The existence of this phenomenon means that there will definitely be consequences caused by progress that occurs, especially in the trade sector. After that, there will also be an impact, especially on the country itself. So the aim of this research is to find out how international trade affects Indonesia's economic prosperity. This research uses a qualitative approach related to international trade and investment on Indonesia's economic prosperity. The results of the research show that the efficiency level of the ASEAN countries taken in the research, Indonesia's efficiency is relatively low. The results of these two studies are related to factors that influence the efficiency of the country's economy, namely international trade and foreign investment. The results of this research show that foreign investment, international trade and financial market development improve a country's economic performance